Design and development of smart emergency light - S. Narasimha; Surender Reddy Salkuti (Universitas Ahmad Dahlan, 2020)
The demand for electricity is increasing day-by-day and frequent power cuts is causing many problems in various areas such as household, domestic, farms, etc. Due to limited amount of power generation at power station and due to shortage of non-renewable sources, uninterruptible power supply being a biggest challenge in the entire world. In this paper, a smart emergency light is designed, developed and tested for use it in various applications such as home, industries, agricultural sector and shops, etc. The developed energy lamp has no running cost and has low initial cost. The main objective of this work is to provide the smart emergency light with solar power to the farmers. This work will help the farmers in many ways such as protecting the fields from yield animals. It can also be used as emergency light and entertainment, etc. The main applications of this work is that it can used as FM radio, USB charging, music by memory card, mini fan, torch light, etc. This can also be controlled by remote. The battery can be used for all these applications. This battery can be charged by two ways using solar energy and AC mains supply. The developed lamp is tested in the real time environment.